Social media-based learning in Chemistry learning: A review - Widarti, Hayuni Retno; Sriwahyuni, Titin; Rokhim, Deni Ainur; Syafrudin, Afis Baghiz (Eclética Química, 2023)
Social media-based learning can involve students in open, competitive, and running learning according to the speed of each understanding. This study aims to examine empirical articles about social media increasing the motivation to study chemistry for high school and undergraduate students using the Systematic Literature Review method, namely, to identify, analyze, and interpret findings on research topics published from 2018 to 2022. Five articles were identified through the publish or perish search engine using Scopus databases. The articles studied reviewed the effect of using social media in learning. The results of the study focused on the use of social media in chemistry learning which can increase student motivation for both high school and undergraduate students.